PLACE-MAKING AFTER DEATH: CONNECTIONS TO PLACE IN THE MEMORIALIZATION PRACTICES OF OLDER ADULTS AND THEIR FAMILIES. (11th November 2018) - Stott, K; Benson, J; Sloan, S; Murphy, S; Halt, A
Abstract: Research has suggested that one way to encourage healthy aging is to construct one's environment in a manner that helps maintain one's identity. Specifically, studies in the field of environmental gerontology posit that the construction of an identifying environment typically includes the process of claiming a place within the space that one resides. Place-making includes both the geographical location and moral ideals that one assigns to the location, and is well established in studies of adults in later life. However, it is less clear how the idea of place-making can extend beyond mortality for older adults and their families. The purpose of this study was to explore how personal connections and attachments to a specific location make the burial/memorialization location(s) a place, rather than simply a space. In this qualitative study, 12 individuals who had lost older family members were interviewed about their experiences of place making in the memorialization of their loved ones. Analyses revealed that participants were attached to the place(s) of memorialization because the location(s) both honored and maintained the identity of the deceased. Additionally, participants also shared that the place(s) of memorialization fostered feelings of the continued presence of, and maintained interactions with, their loved ones, who were deceased. Having a place, or places, that fostered those types of feelings postmortem was crucial for the participants in this study to maintain their connection to the deceased. Practical implications and future directions for research are also discussed.